CUBITAL TUNNEL SYNDROME - Munir, Muh. Ardi (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2015)
Prior to 1957, ulnar neuropathy was felt to be a "stretch neuritis" caused by cubitus valgus. In fact, the predominant cause of ulnar neuropathy was secondary to elbow injuries. Osborne proposed the concept of compression of the ulnar nerve in 1957, with Feindel and StratfordÂ  defining the "cubital tunnel" the following year. Since the advent of more successful orthopedic management of complex elbow injuries, the more frequent cause of ulnar nerve entrapment has become idiopathic or related to a "susceptible" patient. Nonetheless, it appears that ulnar nerve entrapment is increasing in prevalence (although no data are available), with pain often being a predominant morbidity. In 1898, Curtis performed the first published case of management for ulnar nerve neuropathy at the elbow, which consisted of a subcutaneous anterior transposition. (1,2)It is hoped that the reader may develop an increased awareness of cubital tunnel syndrome and its place in the differential diagnosis of the painful upper extremity. An overview of the diagnostic and treatment options are presented, along with complications that may occur. (1,2)